Logistics 4.0: a review of current trends using bibliometric analysis (2022)
The present study aims to analyze the trends on logistics 4.0 literature as well as an overview of the current publications on the subject. Using bibliometric mapping, outputs from Scopus and Web of Science databases were filtered and treated, resulting in a 186 scientific articles sample. Results reinforce the recent nature of the topic and the main trends, as well as indication to future studies. Four categories emerged from each database analysis representing the key topics of current publications. Evidence suggests six key trends to guide future research: theoretical advancements, strategic and competitive impact, context and environmental variables, Big Data and logistics 4.0, technology and information systems applied to logistics 4.0 and managerial aspects.